Exploring the copper(II) coordination to 2′-hydroxy-4-benzyloxychalcone analogues and their potential pharmacological applications - dos Santos Oliveira, Laiane; de Souza Guarda, Pedro Henrique; Rosa, Letícia Bazilio; Rodrigues, Gustavo Clauss; Affonso, Daniele Daiane; de Carvalho, João Ernesto; Santos, Igor Andrade; Harris, Mark; Nakahata, Douglas Hideki; Sabino, José Ricardo; Miguel, Danilo Ciccone; Ruiz, Ana Lucia Tasca Gois; et al. (Elsevier, 2024)
Chalcones are chemical precursors of flavonoids and exhibit a variety of biological properties, including anti-cancer, anti-inflammatory, and anti-malarial activities. According to the literature, different transition metal complexes of chalcones exhibit antitumor and antibacterial properties. Herein we report the synthesis, characterization, and the in vitro evaluation of antileishmanial, antiproliferative, and antiviral activities of novel copper(II)-2′-hydroxy-4-benzyloxychalcone complexes. Two of the complexes (1 and 2) had the formula [Cu(L)2], and the other two (3 and 4) were characterized as [Cu(L)(phen)Cl], where L is the deprotonated form of the 2′-hydroxy-4-benzyloxychalcones (HL1, is a fluorine substituted analog of HL2) and phen is 1,10- phenanthroline. Structures resolved by single-crystal X-ray diffraction showed that complexes 3 and 4 had a distorted square pyramid geometry, with chloride at the apical position. The stability of the complexes in dimethyl sulfoxide showed a significant variation. A wide range of ligand exchange kinetics was observed in the solution, influenced by chalcone fluorination and the presence of phenanthroline. Potential pharmacological applications were evaluated using in vitro assays for anti-proliferative, leishmanicidal, and antiviral activities. Complexes 1 and 3 showed cytostatic effects against the human breast tumor cell line (MCF-7, GI50 = 4.6 and 1.0 µM, respectively) that could be attributed to the free ligand HL1 (MCF-7, GI50 = 1.16 µM). Moreover, complex 1 showed higher selectivity to MCF-7 cells in comparison to murine immortalized 3T3 cells (GI50 > 100 µM). Complex 2 was inactive and toxic while complex 4 showed an unspecific cytostatic effect. Despite a weak leishmanicidal activity, at 25 µM, complex 3 inhibited (85,1 %) the SARS-CoV-2 replication at 2 µM. As complex 4 also showed good antiviral activity against SARS-CoV-2 (84,7 %), the antiviral activity seems to be related to copper(II)-phenanthroline fragment. This work demonstrates how simple changes in the structure of the ligand affect ligand exchange reactions and, consequently biological activity. It also expands the biological applications of Cu(II) chalcone complexes.
Keywords: Anti-SARS-CoV-2; Antitumor; Chalcone; Copper; Metal complexes